Family Alienation and the Challenges of the Technological Age - Alajmi, Amirah Mohammad (Journal of Islamic Sciences, 2024)
The phenomenon of family alienation resulting from technological factors in our current era is considered one of the most psychological and social phenomena that threaten the security and lives of adolescents. Alienation constitutes one of the threats to family cohesion and the elimination of human nature. One of the most important challenges facing the family in our current era is the emergence of the phenomenon of family alienation. The study aimed to explain the phenomenon of family alienation among (spouses and children) in light of the age of technology, and the excessive use of social media, which has become the undisputed concern of individuals, as it was based on meeting their desires. The satisfactions that their souls longed for (chats, dialogues, news) were achieved. No one denies the advantages of social media and the opening of broad horizons in communication and networking, and the elimination of physical and temporal barriers. It is also not permissible to deny the change it has made to traditional methods. Which is based on strengthening family relationships, including (family sessions, meetings, family chats, dialogues, discussions, interaction within the family, and the relationship between spouses), and from here the study came to explain what previous studies have confirmed about the causes of family alienation in light of the age of technology (the age of digitalization). ), where it concluded that the family community has become more empowered in light of the presence of the age of technology, in addition to the fact that families suffer from societal danger and a threat to the family that requires research and income to develop mechanisms to prepare for moderation in the consumption of social networking sites, and in light of these results, the study recommended the necessity of educating individuals Educating the family about what can be done through technology, and directing them towards optimal exploitation of it for the benefit of themselves and their communities.